Irrigation Data Inventory Using Web-Based Geographic Information System to Support the Water Discharge Distribution in Belu Regency - Tetik, Fransiskus Rendi; Kelen, Yosep Pius Kurniawan; Lestari, Anastasia Kadek Dety; Manek, Siprianus Septian (Politeknik Negeri Lhokseumawe, 2025)
The development of information technology in the era of globalization has become an integral part of human life, especially in providing fast, accurate, and easily accessible information. BeluRegency, located in East Nusa Tenggara Province, has challenges in managing air resources, especially related to agricultural irrigation. Inaccurate and incomplete irrigation data hinders the efficiency of water discharge distribution, which is very important or most of the population who make a living in the agricultural sector. This research aims to apply the Geographic Information System (GIS) in the inventory of distributed data, in order to improve the efficiency and effectiveness of air resource management. By using GIS, it is hoped that accurate mapping of the location of irrigation canals can be carried out, making it easier to make decisions regarding the distribution of water discharge. The results of this research are expected to increase agricultural productivity, maintain environmental curiosity, and improve the welfare of farmers and local communities in Belu Regency. This research is entitled Irrigation Data Inventory Using Web-Based Geographic Information System to Support the Water Discharge Distribution in Belu Regency